Permian basin oil and gas recovery conference : reprints - Permian Basin Oil and Gas Recovery Conference (1974 : Midland, Tex.); Society of Petroleum Engineers of AIME (Dallas, Tex. : Society of Petroluem Engineers of AIME, 1974)
51